Construction of Nitrogen‐Doped Carbon‐Coated MoSe2 Microspheres with Enhanced Performance for Lithium Storage. Issue 52 (21st August 2017) - Tang, Wangjia; Xie, Dong; Shen, Tong; Wang, Xiuli; Wang, Donghuang; Zhang, Xuqing; Xia, Xinhui; Wu, Jianbo; Tu, Jiangping
Abstract: Exploring advanced anode materials with highly reversible capacity have gained great interests for large‐scale lithium storage. A facile two‐step method is developed to synthesize nitrogen‐doped carbon coated MoSe2 microspheres via hydrothermal plus thermal polymerization. The MoSe2 microspheres composed of interconnected nanoflakes are homogeneously coated by a thin nitrogen‐doped carbon (N‐C) layer. As an anode for lithium ion batteries, the MoSe2 /N‐C composite shows better reversibility, smaller polarization, and higher electrochemical reactivity as compared to the unmodified MoSe2 microspheres. The MoSe2 /N‐C electrode delivers a high specific capacity of 698 mAh g −1 after 100 cycles at a current density of 100 mA g −1 and good high rate performance (471 mAh g −1 at a high current density of 2000 mA g −1 ). The improved electrochemical performance is attributed to the conductive N‐C coating and hierarchical microsphere structure with fast ion/electron transfer characteristics. Abstract : Microsphere of influence : Nitrogen‐doped carbon‐coated MoSe2 microspheres are constructed by a facile two‐step process. These microspheres as anode materials exhibit superior Li ion‐storage performance.